Large gap two-dimensional topological insulators with the coexistence of a significant Rashba effect and piezoelectricity in functionalized PbGe monolayers. Issue 8 (2nd February 2023) - Shen, Ningyuan; Lei, Shuangying; Wang, Yonghu; Wan, Neng; Chen, Jie; Huang, Qingan
Abstract : PbGe(CN)2 and PbGe(C2 H)2 (PQSHI) are predicted to realize the piezoelectricity, quantum spin Hall (QSH) insulator, and Rashba effects simultaneously. Abstract : In recent years, two-dimensional (2D) multifunctional materials have become a research hotpot for their wide application range. In this work, PbGe(CN)2 and PbGe(C2 H)2 are predicted to realize the piezoelectricity, quantum spin Hall (QSH) insulator, and Rashba effects simultaneously. The topological bandgaps of PbGe(CN)2 and PbGe(C2 H)2 are 0.418 and 0.405 eV, respectively, which are much larger than the recently reported value of 0.165 eV for InTeO that can also attain both the piezoelectricity and QSH insulator (PQSHI) effects. The in-plane and out-of-plane piezoelectric effects coexist in both PbGe(CN)2 and PbGe(C2 H)2 with the in-plane piezoelectric coefficients d 11 of 8.823 and 2.913 pm V −1 and out-of-plane piezoelectric coefficients d 31 of 0.638 and 0.608 pm V −1 . It is worth noting that there are significant Rashba SOC effects in PbGe(CN)2 and PbGe(C2 H)2 and their Rashba splitting parameters are 2.576 and 2.184 eV Å, respectively. The prominent Rashba effects, which don't exist in other PQSHI materials, make PbGe(CN)2 and PbGe(C2 H)2 more suitable for application in spintronic devices. Besides, the topological properties can remain robust under the uniaxial strain within the range of −6% to 6%. Our results imply that PbGe(CN)2 and PbGe(C2 H)2 qualify as potential candidates for low-power, highly sensitive piezoelectric devices, such as pressure sensors for converting mechanical energy into electrical energy.